Workshop Pengelolaan Pojok Baca berbasis Digital bagi Guru SD Tambang - Zufriady; Kurniaman, Otang; Noviana, Eddy; Guslinda; Munjiatun, Munjiatun; Zariul Antosa; Astuti Mulyani, Eva (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
The purpose of this workshop is to provide teacher knowledge and skills in digital-based reading cornersfor teachers as teacher knowledge and skills in managing digital-based reading corners in overcoming the school literacy movement. The method of activities carried out consists of three activities: pre- activity, implementation of activities, and post-activity. The pre-activity activity is an initial assessment activity to obtain the reasons for the teacher/activity participant to take part in the activity. Meanwhile, the activity of implementing the activity was carried out by providing a list of questions to the teacher/participant containing the teacher's initial knowledge about digital literacy. then proceed with the delivery of the material. The third activity is post-activity, which is an activity to process data obtained from the responses of participants/teachers before and after the activity is carried out. The results of the digital-based reading corner management workshop activity can improve the knowledge and skills of teachers in managing reading corners in schools. This can be shown by the active participation of participants in activities starting from the beginning of delivering material that plays an active role until the end of the activity and also the teacher's ability to carry out assigned activities. given two weeks after the workshop was carried out which was proven by the collection of workshop assignments which were uploaded to the google